2013
DOI: 10.1097/bsd.0b013e3182440dce
|View full text |Cite
|
Sign up to set email alerts
|

Three Solutions to a Single Problem

Abstract: Cotrel/Metha casting for infantile scoliosis can be accomplished without a specialized table using commonly available equipment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…While the Mehta protocol is well established, there are some institutions that have opted for non-Mehta tables including Traction Frames, Spica tables, Risser, and OSI tables due to the high costs of purchasing Mehta tables or physician preference. 17,[19][20][21] Physicians have reported successful applications of Mehta castings without using specialized tables, however, these results do not take anesthesia time into consideration. 17,19 Mehta tables are specifically designed to allow for easy access to the pa-tient's body while supporting the head and limbs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the Mehta protocol is well established, there are some institutions that have opted for non-Mehta tables including Traction Frames, Spica tables, Risser, and OSI tables due to the high costs of purchasing Mehta tables or physician preference. 17,[19][20][21] Physicians have reported successful applications of Mehta castings without using specialized tables, however, these results do not take anesthesia time into consideration. 17,19 Mehta tables are specifically designed to allow for easy access to the pa-tient's body while supporting the head and limbs.…”
Section: Discussionmentioning
confidence: 99%
“…17,[19][20][21] Physicians have reported successful applications of Mehta castings without using specialized tables, however, these results do not take anesthesia time into consideration. 17,19 Mehta tables are specifically designed to allow for easy access to the pa-tient's body while supporting the head and limbs. 22 In describing the Mehta casting technique, Sanders states that Risser and Cotrel frames can be used, but their large size is less than ideal for these procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Underlayers previously described include stockinette, 6 , 7 webril, 14 felt on bony prominences and silver impregnated shirt, 8 , 10 pads and splints, 27 or gore pantaloons. 28 The comparative ability of these methods to prevent skin ulceration or improve results remains unknown. For example, a recent study found the addition of adhesive pads increased major curve correction.…”
Section: Discussionmentioning
confidence: 99%